2019
DOI: 10.1007/s40199-019-00263-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation of the effects of boron nitride nanotubes and curcumin on DNA damage

Abstract: Backround Stem cells provide an opportunity to analyse the effects of xenobiotic on cell viability, differentiation and cell functions. Evaluation of the possible cytotoxic and DNA damaging effects on bone marrow CD34 + stem cells is important for their ability to differentiate into blood cells, and also for bone marrow diseases therapy. Boron nitride nanotubes and curcumin are potential nanoformulation agents that can be used together in the treatment of cancer or bone marrow diseases. Therefore, it is import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Thus, even if we cannot exclude that reversible DNA damages could occur through single strand break DNA, the obtained results indicated that BNNT exposure do not lead to permanent DNA alteration. This obser vation is contrary to in vitro studies indicating dis turbances of cell proliferation and genotoxicity of BNNT (Fernandez-Yague et al 2015;Horvath et al 2011;Çal and Bucurgat 2019;Emanet et al 2015), but consistent with the few available works per formed in vivo. lndeed, no genotoxicity was observed in the planaria (Salvetti et al 2015) as well as in drosophila (Demir and Marcos 2018) after BNNT exposure.…”
Section: Micronucleus Assay and Ce// Cycle Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, even if we cannot exclude that reversible DNA damages could occur through single strand break DNA, the obtained results indicated that BNNT exposure do not lead to permanent DNA alteration. This obser vation is contrary to in vitro studies indicating dis turbances of cell proliferation and genotoxicity of BNNT (Fernandez-Yague et al 2015;Horvath et al 2011;Çal and Bucurgat 2019;Emanet et al 2015), but consistent with the few available works per formed in vivo. lndeed, no genotoxicity was observed in the planaria (Salvetti et al 2015) as well as in drosophila (Demir and Marcos 2018) after BNNT exposure.…”
Section: Micronucleus Assay and Ce// Cycle Analysissupporting
confidence: 81%
“…Studies related to BNNT toxicity remain scarce and inconsistent. lndeed, although many of the published works indicate biocompatibility of raw and functionalized BNNT in vitro as well as in vivo (Chen et al 2009;�en, Emanet, and Çulha 2016;Ciofani et al 2010;Ciofani et al 2008;Ciofani et al 2014;Fernandez-Yague et al 2015;Rocca et al 2016;Salvetti et al 2015), some studies highlighted cell type dependent cytotoxic and genotoxic effects (Augustine et al 2019;Horvath et al 2011;Çal and Bucurgat 2019). Ecotoxicological data are lacking while it is necessary for the sustainable develop ment of BNNT-based products.…”
Section: Introductionmentioning
confidence: 99%
“…In the selected articles various methods have been used to analyse the effects of the BNNTs-incubated cells on cell viability and cytotoxicity assays (Figure 4a). The most commonly used evaluations were 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) [31,35,76,78,82,156], 2-(4-iodophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2Htetrazolium (WST-1) [68], alamarBlue™ [30], Trypan Blue assay [78,82] [27], lactic dehydrogenase (LDH), and amido black assay [67]. These assays are calorimetric methods to evaluate cell viability, proliferation, and cytotoxicity.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…Genotoxicity testing is performed to detect and identify hazards, and to determine the mutation of germ cells and cancer development (Figure 4b) [46]. The genotoxicity of BNNTs can be assessed using the comet assay [35,40,57]. The comet assay can be used with in vivo and in vitro evaluation of genotoxicity.…”
Section: Genotoxicity Evaluationmentioning
confidence: 99%
See 1 more Smart Citation